Public Transport Integration as a Strategy to Reduce Emissions in Jakarta - Harris, Mohammed Osvaldo Moreno (Siber Journal of Transportation and Logistics, 2025)
Jakarta faces severe air pollution, largely driven by emissions from private vehicles. As the city continues to urbanize and motorization increases, the integration of public transport modes emerges as a crucial strategy to mitigate environmental impact. This study explores how the integration of various public transport systems such as MRT, LRT, TransJakarta, and KRL can reduce greenhouse gas emissions by shifting commuter preferences away from private vehicles. Using a mixed methods approach that combines emission data analysis, transportation usage statistics, and user surveys, this paper evaluates the current state of transport integration and its impact on emission reduction. The findings suggest that better connectivity, unified ticketing systems, and improved intermodal access significantly encourage public transport use and lead to measurable emission reductions. Despite challenges such as institutional fragmentation and infrastructure gaps, policy recommendations are proposed to support a fully integrated, sustainable urban transport system in Jakarta. This paper contributes to the growing body of literature on urban mobility and environmental sustainability in rapidly developing megacities.